2012
DOI: 10.22610/jebs.v4i7.341
|View full text |Cite
|
Sign up to set email alerts
|

Development and Growth through Economic Diversification: Are there Solutions for Continued Challenges Faced by Brunei Darussalam?

Abstract: Since its independence in 1984, the government of Brunei Darussalam has made economic diversification as its prime economic agenda to decrease its heavy dependence on oil and gas industry. The oil and gas industry has significantly contributed in the present level of economic prosperity of this small nation of 0.4 million people. However, being a very capital intensive industry it offers few job opportunities. The majority of the local population relies on better paid government jobs in the non-oil sector. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Recent research conducted by Varghese (2011) on SME's suggested that economic diversification primarily depend on the SME segment. The importance of economic diversification was further highlighted by Siddiqui and Al Athmay (2012) in their research on the Brunei economy, which is highly dependent on the oil industry. They observed that Brunei's current unemployment rate was 12% and that this was largely due to a lack of private sector investment in industries other than oil and gas.…”
Section: Review Of Related Literature 21 Conceptual Review 211 Ecomentioning
confidence: 99%
“…Recent research conducted by Varghese (2011) on SME's suggested that economic diversification primarily depend on the SME segment. The importance of economic diversification was further highlighted by Siddiqui and Al Athmay (2012) in their research on the Brunei economy, which is highly dependent on the oil industry. They observed that Brunei's current unemployment rate was 12% and that this was largely due to a lack of private sector investment in industries other than oil and gas.…”
Section: Review Of Related Literature 21 Conceptual Review 211 Ecomentioning
confidence: 99%
“…While a number of authors have proposed such transformation for Brunei, none have described the construction boom needed to bring such a structuring into existence. Siddiqui () has described Brunei's highly oil‐reliant economy and prospects for diversification. Gollin, Jedwab, and Vollrath () have noted that the industrialization of Brunei (and other places) is likely to bring about urbanization.…”
Section: Need For Fundamental Economic Change In Order To Achieve Fasmentioning
confidence: 99%
“…The importance of innovation seems to resonate with the government of Palestine as evidenced by its inclusion in the national development plan. A proper structure, policies and systems need to take place in institutional spheres (Siddiqui and Al Athmay, 2012). One such structure is the collaboration between government, universities and industry (Etzkowitz, 2003).…”
Section: Introductionmentioning
confidence: 99%